This Phenomenon Sustainable Competitive Advantage for Alor Island Ecotourism Development: Background Review and Literature Review - Awang, Mesak Y. (Journal of International Conference Proceedings, 2023)
Various research results regarding ecotourism development has been carried out, but only a little research had been carried out on Alor Island. This results in the literature on this topic not being sufficient as a supporting theory. Therefore, there is a need to understand the resources that contribute to Alor Island's competitive advantage. The research method used is qualitative with a descriptive approach, through document and literature studies at national and regional levels related to the research theme, namely sustainable ecotourism. This research fills this gap with a Resource-Based View approach. The main objective of this research is to develop a sustainable competitive advantage for ecotourism development on Alor Island. This research reviews the background and previous literature regarding the definition of ecotourism, sustainable tourism development, resource view, dynamic capabilities, and sustainable competitive advantage.